Influence of screw channel angulation on reverse torque value and fracture resistance in monolithic zirconia restorations after thermomechanical cycling: an in-vitro study - Amir Alireza Khaledi; Shouka Shalileh; Maryam Hejazi; Rashin Giti (BMC, 2024)
Abstract Background While the concept of angled screw channels has gained popularity, there remains a scarcity of research concerning the torque loss and fracture strength of monolithic zirconia restorations with various screw channel angulations when exposed to thermomechanical cycling. This in-vitro study aimed to evaluate the reverse torque value and fracture resistance of one-piece screw-retained hybrid monolithic zirconia restorations with angulated screw channels after thermomechanical cycling. Methods One-piece monolithic zirconia restorations, with angulated screw channels set at 0°, 15°, and 25° (n = 6 per angulation) were fabricated and bonded to titanium inserts using a dual-cure adhesive resin cement. These assemblies were then screwed to implant fixtures embedded in acrylic resin using an omnigrip screwdriver, and reverse torque values were recorded before and after thermomechanical cycles. Additionally, fracture modes were assessed subsequent to the application of compressive load. One-way ANOVA and Bonferroni post hoc test were used to compare the groups (α = 0.05). Results The study groups were significantly different regarding the fracture resistance (P = 0.0015), but only insignificantly different in the mean percentage torque loss (P = 0.4400). Specifically, the fracture resistance of the 15° group was insignificantly higher compared to the 0° group (P = 0.9037), but significantly higher compared to the 25° group (P = 0.0051). Furthermore, the fracture resistance of the 0° group was significantly higher than that of the 25° group (P = 0.0114). Conclusions One-piece hybrid monolithic zirconia restorations with angulated screw channels can be considered an acceptable choice for angulated implants in esthetic areas, providing satisfactory fracture strength and torque loss.